PENGARUH BAURAN PEMASARAN DAN WORD OF MOUTH (WOM) TERHADAP MINAT BELI ULANG - Ahmad Sahrir; Hasanuddin Bua; Endro Sukotjo (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
The objectives of this study are: 1.) To determine the effect of marketing mix variables that include products, prices, places and promotions, on the repurchasing interest of independent broiler SME consumers in Konawe Selatan. 2.) To determine the effect of word of mouth (WOM) variables on the repurchasing interest of UKM chicken consumers in Konawe Selatan. 3.) To find out whether the marketing mix and word of mouth can affect repurchasing interest of UKM chicken consumers in Konawe Selatan. The method used in this sampling was non-probability sampling technique, the type of non-probability sampling used was purposive sampling. Data collection was carried out by distributing questionnaires. Researcher determined purposive sampling due to unknown population numbers, so the researcher used Roscoe's formula and determined sample of 60. The researcher used IBM SPSS 21.0 for Windows to support existing primary data. The results of the study shows that: (1). The marketing mix and word of mouth have positive and significant effects on the repurchasing interest of UKM chicken consumers in Konawe Selatan. (2). The marketing mix has positive and significant effects on the repurchasing interest of UKM chicken consumers in Konawe Selatan. (3) word of mouth has positive and significant effects on the repurchasing interest of UKM chicken consumers in Konawe Selatan. For further research, researcher suggest using other variables, such as variables of satisfaction, loyalty and company image.Keywords: marketing mix, word of mouth, repurchasing interests